A precise goniometer/tensiometer using a low cost single-board computer. (21st November 2017) - Favier, Benoit; Chamakos, Nikolaos T; Papathanasiou, Athanasios G
Abstract: Measuring the surface tension and the Young contact angle of a droplet is extremely important for many industrial applications. Here, considering the booming interest for small and cheap but precise experimental instruments, we have constructed a low-cost contact angle goniometer/tensiometer, based on a single-board computer (Raspberry Pi). The device runs an axisymmetric drop shape analysis (ADSA) algorithm written in Python. The code, here named DropToolKit, was developed in-house. We initially present the mathematical framework of our algorithm and then we validate our software tool against other well-established ADSA packages, including the commercial ramé-hart DROPimage Advanced as well as the DropAnalysis plugin in ImageJ. After successfully testing for various combinations of liquids and solid surfaces, we concluded that our prototype device would be highly beneficial for industrial applications as well as for scientific research in wetting phenomena compared to the commercial solutions.